La dimension symbolique des TIC et l’auto-réalisation collective - Mayhoua MOUA (Tic & Société)
Natives of China, the Hmong are an ethnic minority which, in the course of its history, has often experienced migration and cohabitation with larger populations and cultures. Thirty years after their installation in West, mainly in the United States and in France, discourses referring to the Hmong are multiplying on Internet through sites, newsgroups or blogs. What is the future of minority identities in a context of the transnationalisation of cultures ? What does it mean for a community like the Hmong to connect on the global communication network that is the Internet ? Using the idea of « shared community », I will analyse how the symbolic universe of information and communication technologies articulates with the aspirations of collective self-realization of a diaspora such as the Hmong.